Co-design of an optimal distance learning model adapted to rural areas of Morocco in primary school - Alladatin, Judicaël; Al-chikh, Insaf; Mimoudi, Aziz; Chebak, Ahmed (STAI Miftahul Ula Nganjuk, 2024)
This participatory research aims the co-design of an optimal distance education system adapted to rural areas, in collaboration with local stackholders. We adapted semi-structured interviews with each group (school principals, teachers, students, parents) that allowed us first to evaluate the teaching models used in their environment. Secondly, with a collaborative working group, the results of the analysis are used to identify and plan corrective actions for these models. The outcome of the corrective actions allowed us to co-design in each school an optimal 3D model to improve the performance and use of distance or hybrid teaching practices. The idea of the designed model is to set an internet generator in the schools to provide good network to the whole region. The stakeholders also designed their specific tablet, which is connected to an intranet, and that only works between the school and the students’ devices, ensuring that the student would not have access to any other content than education. The teacher will have a similar device, he will receive the students' comments, and he will be able to clarify or answer the students’ questions individually or in groups, online or during the face-to-face lesson. Students wanted their device to be uploaded with interactive lessons to make them feel like they were in a genuine class. In addition, they wanted parental aid during the home study process.